Magnetohydrodynamics squeeze flow of sodium alginate-based Jeffrey hybrid nanofluid with heat sink or source - Nur Azlina Mat Noor; Sharidan Shafie (Case Studies in Thermal Engineering, 2023)
The behavior of magnetohydrodynamics (MHD) flow, heat and mass transfer of Jeffrey hybrid nanofluid on the squeeze channel through permeable medium are discovered. The impacts of chemical reaction and heat sink/source are considered. The dimensionless equations are discretized by employing similarity transformation and Keller-box techniques. The dispersion of Copper (Cu) and Alumina (Al2O3) in the base fluid of sodium alginate (C6H9NaO7) are considered. The validation of the current outputs by comparing with existing outputs from reputable papers is conducted. The discussion on the velocity, temperature and concentration, and physical quantities of fluid are reviewed based on the graphical outputs with the effects of chemical reaction, Jeffrey fluid, magnetic, porous medium, nanoparticles volume fraction and heat sink/source. The graphical results shows the wall shear stress elevates for S and Ha, while it dropping for De, λ1 and Da. The fluid velocity accelerates caused by squeezing of two surfaces, while it decelerates with increase in De,Da and φ2 at the centre of channel. The resistance due to Ha and λ1 in the flow decrease the fluid velocity near the lower channel. The increment of convective heat transfer and temperature occurs with γ and Ec rises. The constructive chemical reaction and volume fraction of copper boosts the concentration and decrease the mass transfer rate of fluid flow, whereas adverse impact is discovered for destructive chemical reaction.